Centros de memória e documentação da Universidade Federal de Minas Gerais: perfis institucionais e políticas de acervo - Thais Nodare de Oliveira (2016)
This study addresses the memory and documentation centers that are part of the Rede de Museus e Espaços de Conhecimento of the Federal University of Minas Gerais (UFMG). The main objective of this research was to understand the trajectory of these memory and documentation centers. To this end, we sought to understand the context of the creation of these centers, the process of acquisition and the processing assets, with emphasis on the experience of the Centro de Memória da Educação Física, do Esporte e do Lazer (Cemef/UFMG).Thus, this work aims to contribute to the field of Archivology, especially in relation to the dialogue established between memory and documentation centers and archival policies. To analyze the centers, management documents found in their own centers and reports of the Memory Project at UFMG were mobilized, what shows the first attempts to establish a document management at the University. From reading and analyzing all this documentary corpus and interviews made withpeople who had some relation with the centers coordination, it was possible to identify that the analyzed memory and documentation centers have distinct vocations with regard to the origin, the composition and the treatment of the collections and that it proceeds from a political choice of the institution.